Studi Perbaikan Pengelolaan Perpustakaan dan Sistem Pengelolaan Arsip & Dokumen di PT Badak - Iman Satoto, Kodrat; Fatchur Rochim, Adian; Christyono, Yuli; Handayani, Tri; Taufiq, Amin; Suharso, Putut (JURNAL SISTEM KOMPUTER, 2011)
Library at PT Badak LNG Bontang East Kalimantan, store various types of collections such as contract documents, agreements, plant & equipment manuals, reference books, textbooks, technical brochures, documents and data supporting the project, certification documents, images refinery engineering techniques & equipment, magazines, journals and other collections. At this time the library management is still done manually, although some have been made in electronic information systems. Besides the libraries, archives and document management systems need to be improved to support the needs of the organization. From the results of auditing the International Safety Rating System (ISRs) conducted by Det Norske Veritas (DNV), the management of archives and documents need to be improved, especially for the storing and retrieval system for archives and documents can be done quickly and accurately. Utilization of information technology has also been applied, but need to be evaluated in order to meet the needs of each user. The document has been categorized as non-active documents, removed from their respective departments to the Records Center at the Department of Services to follow rules archive retention policy. While the document is still classified as active are still kept by each department. Creation, storing, organization and management of existing documents need to be thoroughly evaluated to facilitate storing and retrieval document fast and accurate.Index Terms — Library, Archive Storage, Retrieval System